2018
DOI: 10.21608/zvjz.2018.14385
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Cell-Free Supernatant Inhibits Hyphal Morphogenesis and Biofilm Formation in Candida albicans

Abstract: Enterococcus faecalis and Candida albicans are two of the most significant opportunistic and intricate nosocomial pathogens. They reside overlapping niches as major constituents of the gastrointestinal (GI) and oral microbiome. This study was designed to investigate the interaction between these two opportunistic pathogens that could affect treatment strategies and influence the interkingdom signaling and sensing in the microbiome conceptions. E. faecalis was isolated from 150 samples collected from human urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…In this new study we describe changes in C. albicans growth, phenotype, virulence and transcriptome when co-cultured with E. faecalis in vitro . In agreement with previous in vitro and in vivo studies, our preliminary investigation showed an inhibition of C. albicans growth, hyphal morphogenesis and biofilm formation in dual-species biofilms [ 18 , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Subsequent RNASeq showed that E. faecalis rapidly and significantly alters C. albicans gene expression.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this new study we describe changes in C. albicans growth, phenotype, virulence and transcriptome when co-cultured with E. faecalis in vitro . In agreement with previous in vitro and in vivo studies, our preliminary investigation showed an inhibition of C. albicans growth, hyphal morphogenesis and biofilm formation in dual-species biofilms [ 18 , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Subsequent RNASeq showed that E. faecalis rapidly and significantly alters C. albicans gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…First, we investigated the general effect of E. faecalis on C. albicans hyphal morphogenesis, biofilm formation, growth, and expression of key genes related to biofilm formation, virulence and drug resistance. C. albicans SC5314, HBF and LBF were grown in mono-species biofilms or co-cultured with E. faecalis ER5/1 for 24 h. As reported by various studies [ 33 , 34 , 36 , 38 , 39 ], C. albicans hyphal morphogenesis was shown to be clearly inhibited in co-cultures, as shown in calcofluor stained images ( Fig. 1 a).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Clove and cinnamon EOs (Sigma Aldrich, St. Louis, MO, USA) were diluted in 1% dimethyl sulfoxide (DMSO, Sigma) (Shahzad et al, 2014). The CFS of E. faecalis used in this study was purified using ammonium sulfate precipitation and dialysis from two strains in our previous study (Hassan et al, 2018). These strains were isolated from cheddar cheese (CFS1) and chicken intestine (CFS2) samples.…”
Section: The Tested Essential Oils Biological and Chemical Agentsmentioning
confidence: 99%